Pengaruh Pemahaman Akuntansi, Modal Usaha, Kreativitas, dan Pemanfaatan Media Sosial Terhadap Keberlanjutan UMKM di Kota Malang - Anisa Maratus Solikha; Moh. Amin; Umi Nandiroh (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study is to ascertain the impact of accounting knowledge, financial resources, creativity, and social media use on the sustainability of UMKM in the Malang City. The dependent variable in this study is the sustainability of UMKM in Malang City, and the independent factors include of accounting, business capital, innovation, and usage of social media. Because the data employed in this type of research is in the form of numbers and numbers, it is a quantitative type of study. Primary data were used in this study, and a questionnaire was used to gather the data.  The participants in this study are UMKM actors who registered with Malang City’s Office of Corporations, Industry, and Trade. The slovin formula is employed in the data collection process. Based on this methodology, 90 respondents from the UMKM actors were used. The multiple linear regression analysis test, instrument test, normality test, traditional assumption test, and hypothesis test were all employed to assess the hypothesis, classic assumption test, multiple linear regression analysis test, and hypothesis test. The result showed that are accounting comprehension variable had no effect on UMKM sustainability, while the venture capital variable had a positive and significant effect on UMKM sustainability, while the creativity variable had no effect on UMKM sustainability and the social media utilization variable has a significant and significant affect on the sustainability of UMKM.Keywords: Understanding Of Accounting, Business Capital, Creativity, Utilization of Social Media, UMKM Sustainability.